An Empirical Evaluation of Devolving Administrative Control to Costa Rican Hospital and Clinic Directors. (April 2015) - Lee, Theodore; McKee, Douglas
In the early 2000s, Costa Rica implemented comprehensive reforms of its health care system, including devolving administrative power from the central government to some providers that remain part of the national system. In this article, we evaluate how this aspect of the reform affected clinic efficiency and population health by analyzing administrative data on regional providers and mortality rates in local areas. We compare changes in outcomes across time between areas that signed performance contracts with the central government and received limited budgetary control to those that continued to be managed directly by the central government. We believe the reform created opportunities for providers to become more efficient and effective. Our results suggest that the reform significantly decreased costs without adversely affecting quality of care or population health.